Hisonotus pachysarkos, a new species of cascudinho from the rio ivaí basin, upper rio paraná system, Brazil (Loricariidae: Otothyrinae) - Zawadzki, Cláudio H.; Roxo, Fábio F. [UNESP]; Da Graça, Weferson J. (My University, 2016)
Hisonotus pachysarkos, new species, is described from rio Ivai basin, upper rio Parana system. The main characters used to distinguish it from congeners are: (1) the completely naked abdomen; (2) large males (about than 35.0 mm SL) with swollen ventral surface of the head and abdomen; (3) the absence of an odontode-free band on anterior margin of the snout; (4) the absence of a conspicuous tuft of enlarged odontodes on posterior tip of parieto-su- praoccipital; (5) males with a shorter unbranched pectoral-fin ray, not reaching half of the unbranched pelvic-fin ray; (6) the absence of contrasting dark geometric spots on the anterodorsal region of the body; and (7) the yellowish tipped teeth. Hisonotus pachysarkos is widely distributed in the medium and upper portions of the rio Ivai basin and it is found in the marginal or submerged aquatic vegetation.